Correlation of level of haemoglobin with body mass indexAmong adolescent girls with iron deficiency anemiaUndergoing nutritional support therapy - S.RESMI,; Dr. FATHIMA LATHEEF,; Dr. R.VIJAYARAGHAVAN, (International Journal of Pharma and Bio Sciences, 2017)
The aim of the study is to correlation of haemoglobin with body mass index among adolescent girls with iron deficiency anemia undergoing nutritional support therapy at selected higher secondary schools in Bangalore Karnataka. Considerable changes in the growth pattern, lifestyle, dietary habits & behaviour are likely to influence the haemoglobin levels among adolescent girls. Body mass index is reliable indicator of health and nutritional status of human beings. It express the relationship between the most widely used parameters to monitor linear and height and weight. Haemoglobin concentration is an important diagnostic indicator for well being of an individual. The total amount of the haemoglobin requirements in the body increases more in boys than in girls at puberty. Menstruation is the main cause of blood loss in women. In present study an attempt has made to study the correlation of haemoglobin with body mass index among adolescent girls with iron deficiency anemia. 120 adolescent girls aged between 14- 17 years studying at Gangothri public school and Srigandhadakaval public school were taken for the study Anthropometric measurements were done using standard protocol. Haemoglobin is estimated by using automatic hematology analyser machine. The karl pearson’s correlation coefficient was carried out to correlate relationship between haemoglobin concentration and body mass index. showed that in the experimental group the correlation between the level of haemoglobin and body mass index in the post test was r=0.067(p=0.609) which was significant. There was a positive correlation between level of haemoglobin and BMI among adolescent girls with iron deficiency anemia.